Peran Komunikasi Organisasi dalam Meningkatkan Branding Fakultas Melalui Media Sosial - Sofiera Amalia; Tyas Cahya Rahmadani; Nor Fatmah (Edumulti: Jurnal Rumpun Ilmu Pendidikan Multidisiplin, 2025)
This article discusses the role of organizational communication in improving faculty branding through social media. Social media is now an important tool for faculty to build an image and introduce themselves to students, prospective students, and the wider community. Effective communication through social media allows faculty to convey information quickly, engagingly, and interactively. Consistent, creative, and relevant content can increase the audience's awareness and trust in the quality and excellence of the faculty. In addition, social media also facilitates the establishment of closer relationships between faculty and audiences through direct interaction. A planned and adaptive communication strategy is essential in utilizing social media as a means of strengthening faculty branding. Social media is not only a promotional tool, but also an effective medium to build the reputation and competitiveness of the faculty in the midst of increasingly fierce competition in the world of education. The emphasis on content management and interaction on social media has been proven to be effective in the branding process, as well as found in various studies on digital branding and the role of social media in building an organization's image.